2023
DOI: 10.1038/s41545-023-00245-x
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on LDH-based catalysts to activate persulfates for the degradation of organic pollutants

Abstract: Degradation of organic contaminants into less toxic substances is the best option to remove these compounds rather than using conventional techniques. The sulfate radical-based-advanced oxidation process is an effective strategy that degrades organic contaminants by activating peroxymonosulfate (PMS). Such a strategy generates singlet oxygen (1O2), hydroxyl ($$^ \bullet \!{{{\mathrm{OH}}}}$$ ∙ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 174 publications
0
10
0
Order By: Relevance
“…Co-precipitation and mechanosynthesis are well-known approaches for the important production of other types of inorganic (nano)materials, 16,[30][31][32][33][34] and yields of several kilograms (410 kg) are achievable goals for satisfying LDH production, [9][10][11][12][13][14][15][16][17][18]30 taking into account the continuous improvement of reactor design and controlled parameters benefiting from past feedback. One can also note the relatively reduced energy demand involved during the first step of coprecipitation as compared to mechanosynthesis, the first occurring generally at low temperature (typically at room temperature), contributing to a cost-effective approach.…”
Section: Perspective Materials Advancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-precipitation and mechanosynthesis are well-known approaches for the important production of other types of inorganic (nano)materials, 16,[30][31][32][33][34] and yields of several kilograms (410 kg) are achievable goals for satisfying LDH production, [9][10][11][12][13][14][15][16][17][18]30 taking into account the continuous improvement of reactor design and controlled parameters benefiting from past feedback. One can also note the relatively reduced energy demand involved during the first step of coprecipitation as compared to mechanosynthesis, the first occurring generally at low temperature (typically at room temperature), contributing to a cost-effective approach.…”
Section: Perspective Materials Advancesmentioning
confidence: 99%
“…35 The main drawbacks in co-precipitation and mechanosynthesis generally include more than four synthesis parameters to control. 2,4,[9][10][11][12][13][14][15][16][17] Synthesis times for co-precipitation vary between a few minutes to more than 8 h, depending on the LDH composition, the nature of intercalation compounds and above all, the crystallization degree expected. The synthesis time for mechanosynthesis is longer, typically more than 12 hours, although studies have reported milling times of less than 1 hour.…”
Section: Perspective Materials Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, x values between 0.20 and 0.33 are more favourable for the formation of well-structured LDH materials. 13,14 A is the anion inserted between the layers of LDHs (see Scheme 1), and this structure can be understood easily via comparison with brucite, Mg(OH) 2 , which is composed of hydroxy-coordinated octahedral units. In the framework of the synthesized LDH materials, partial Mg 2+ could be replaced by M 3+ with a similar radius to Mg 2+ (0.072 nm) and interlayer anions, such as CO 3 2− , NO 3 − , Cl − , etc.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the Advanced Oxidation Process (AOP) is a promising alternative method for degrading synthetic dyes and organic complexes. Simply, AOPs employ high reactive oxygen species (ROS) such as hydroxyl radicals (*OH) and superoxide radicals (*O 2 ‐ ) to decomposition of organic residuals into less harmful compounds or mineralize them totally into carbon dioxide (CO 2 ) and water vapour (H 2 O) [10,11] . Recently, the semiconducting metal oxide‐based photocatalytic degradation of organic/pharmaceutical contaminants has attracted significant attention due to the formation of plentiful reactive radicals during the photodegradation process.…”
Section: Introductionmentioning
confidence: 99%